Experiences in the Introductory Course of Physics for Civil Engineering Students at UMCC - Espinosa, T.; Mazorra, J. (Revista Cubana de Física, 2010)
The start-up level of the fresh man students is one of the main factors that influences the low-results of efficiency in General Physics in the University in Matanzas “Camilo Cienfuegos”. One of the aspects that has to do with this problem is the current differences between the real levels of the students with which they access higher education and the one expected in their curricula. Until very recently the real mastering of the students’ knowledge that will ensure their successful performance within the program was not taken into account, assuming that they master that knowledge in the required level. The need of a differentiated treatment for the students has been understood, as compulsory, corresponding with their kills and knowledge. In this research paper the antecedents, methodological foundation and experiences of a syllabus for a Physics Introductory Course for the Civil Engineering major are presented. This course intends to become an orientation of the study of the discipline based on the development of their learning skills, the logic and language of this science.